2022
DOI: 10.1038/s41598-022-06580-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring protective associations between the use of classic psychedelics and cocaine use disorder: a population-based survey study

Abstract: Cocaine Use Disorder (CUD) is a significant public health problem associated with elevated morbidity and mortality within the United States. Current behavioral treatments have limited efficacy and there are currently no FDA approved pharmacological treatments for CUD. Classic psychedelics might be associated with lowered odds of substance misuse and may effectively treat various forms of addiction. Thus, the goal of this study is to assess protective associations that lifetime use of classic psychedelics may s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 62 publications
2
20
0
1
Order By: Relevance
“…Psilocybin was the sole classic psychedelic substance associated with lowered odds of past year OUD in a large, nationally-representative sample of the U.S. population. These findings accord with other population-based survey research indicating that classic psychedelics share differing relationships to mental health outcomes in naturalistic contexts 16 19 . Additionally, the magnitude of the association between psilocybin use and OUD (30% reduction in odds) is comparable to that initially reported by Pisano et al using NSDUH data from 2008 to 2013—allowing us to report that Pisano et al’s findings replicate in a different (more recent) nationally-representative sample.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Psilocybin was the sole classic psychedelic substance associated with lowered odds of past year OUD in a large, nationally-representative sample of the U.S. population. These findings accord with other population-based survey research indicating that classic psychedelics share differing relationships to mental health outcomes in naturalistic contexts 16 19 . Additionally, the magnitude of the association between psilocybin use and OUD (30% reduction in odds) is comparable to that initially reported by Pisano et al using NSDUH data from 2008 to 2013—allowing us to report that Pisano et al’s findings replicate in a different (more recent) nationally-representative sample.…”
Section: Discussionsupporting
confidence: 90%
“…It is also necessary to understand the unique associations that individual classic psychedelics share with OUD. Work from Jones and Nock 16 19 found that different psychedelic compounds have differing patterns of association with mental health outcomes. Thus, examining the correlates between lifetime use of several commonly-used psychedelic compounds and OUD can help to identify the specific compounds best suited to treating OUD.…”
Section: Introductionmentioning
confidence: 99%
“…These findings also are consistent with other population-based survey research on classic psychedelics suggesting that naturalistic use of LSD in particular is associated with increased odds of adverse outcomes 21 , 22 , despite evidence for LSD’s therapeutic efficacy under clinical administration 23 . Negative outcomes have been associated with the use of some psychedelics, such as paranoia, stress, anxiety, and increased odds of psychosis 24 , and might underlie the association between LSD use and increased odds of nicotine dependence.…”
Section: Discussionsupporting
confidence: 89%
“…These covariates not only mirror those from Simonsson et al (2021aSimonsson et al ( , 2021bSimonsson et al ( , 2021c, which we sought to replicate and extend, but also broadly match those from other population-based survey research on classic psychedelics (Hendricks et al, 2015(Hendricks et al, , 2018Jones, Ricard, et al, 2022;Jones and Nock, 2022a, 2022b, 2022c, 2022d. Furthermore, these variables control for a wide range of potentially confounding sociodemographic and substance use factors known to influence health outcomes (Christensen et al, 2018;Hu et al, 2017;Inoue-Choi, Shiels, et al, 2019;Levola et al, 2020).…”
Section: Control Variablesmentioning
confidence: 85%